Household Risk, Self-Insurance and Coping Strategies in Urban Argentina - World Bank (Washington, DC, 2013)
This study aims to analyze how economic shocks and macroeconomic volatility affect urban Argentine households, the mechanisms that households employ to survive economic crises, and how successful these tools are. Particular attention is given to the structure and wealth of the household and the gender roles of its members. The report identifies how to strengthen the risk management tools to better weather future crises. First, it identifies areas where the government can strengthen mechanisms used by households to insure against the risk of income loss due to a macroeconomic crisis or to cope with such loses when they do occur. Second, the report addresses the appropriate role of the government in providing assistance when risk management by the household is absent or is not adequate. Finally, recognizing that some household reactions to income loss have important long term unintended negative effects, the report recommends on how to discourage such costly behaviors. Among the findings of the study are: Households are not able to perfectly smooth consumption across periods of economic volatility; thus, some adjustment is needed even by the rich. No evidence exists that the macroeconomic policies of the 1990s are directly responsible for changes in manufacturing wages for skilled and unskilled workers. Many Argentines insure against the risk of negative income shocks by having mutiple jobs, and they turn to their families when needed.